Робітництво повітового міста: заводські робітники Луганська у трудових конфліктах і революційних хвилях під час Першої російської революції та Першої світової війни - Гаухман, М. (Місто: історія, культура, суспільство, 2017)
Стаття присвячена колективним діям заводських робітників одного із центрів індустріального Донбасу – повітового міста Луганська – в трудових конфліктах під час Першої російської революції (1905–1907 рр.) та Першої світової війни (1914–1918 рр.). The article deals with the collective actions of plant workers in Luhans’k (in Russian pronunciation – Lugansk) in labor conflicts during the First Russian revolution (1905–1907) and the First World War (1914–1918). This town was the one of the main towns of industrial Donbass and the center of Slovianoserbian district of Ekaterinoslavian province. The relationships between administration and workers in Luhans’k are investigated on the materials of clerical work of Ekaterinoslavian province and memoirs of participators on events. These sources are especially about the behavior of workers from two big industrial enterprises – the Gartman plant and the Cartridges plant. In the crisis periods, such as revolutions and wars, the social-political relations are sharpened and changeable. And revolutions and wars left behind enough historical sources for studying workers’ history.